Visual and keratometric outcomes of keratoconus patients after sequential corneal crosslinking and topography‐guided surface ablation: Early United States experience. Issue 8 (August 2018) - Nattis, Alanna; Donnenfeld, Eric D.; Rosenberg, Eric; Perry, Henry D.
Abstract : Purpose : To evaluate a sequential treatment algorithm for visual and keratometric improvement in keratoconus patients after corneal crosslinking (CXL) followed by topography‐guided photorefractive keratectomy (PRK). Setting : Ophthalmic Consultants of Long Island, Garden City, New York, USA. Design : Retrospective case series. Methods : This study reviewed patients with keratoconus who had CXL followed by custom topography‐guided PRK between April 2016 and December 2016. The following data were collected at baseline, the time of CXL, and 3 months and 6 months after PRK: uncorrected (UDVA) and corrected (CDVA) distance visual acuities, keratometric astigmatism, spherical equivalent, maximum and mean keratometry readings, and corneal thickness at the cone apex. Demographic data, age at time of CXL and PRK, and time elapsed between CXL and PRK were analyzed for significance and a correlation with visual and astigmatic outcomes. Results : The study comprised 56 patients (62 eyes), 34 who had both topographic and refractive treatment and 28 patients who had treatment of topographic irregularities only. The mean age was 38.08 years ± 13.07 (SD) at CXL and 40.33 ± 13.44 years at topography‐guided PRK. Six months after PRK, there was a significant improvement in UDVA and CDVA in the refractive group (20/60 and 20/30, respectively) versus the nonrefractive group (20/100 and 20/40, respectively). Ninety‐three percent of eyes that had refractive treatment had 20/40 or better CDVA. There were no significant adverse events in any case. Conclusions : The data support the use of refractive treatment in addition to topographic treatment for visual improvement in patients with keratoconus having CXL and PRK.